Facile one-pot green synthesis of magnetic separation photocatalyst-adsorbent and its application. (June 2022) - Cheng, Song; Zhao, Saidan; Xing, Baolin; Shi, Changliang; Meng, Weibo; Zhang, Chuanxiang; Bo, Zhang
Abstract: Magnetic separation photocatalyst-adsorbent (MSPA) is successfully prepared by pyrolysis of cotton stem for rhodamine B and malachite green wastewater removal using one-pot method. The results show that MSPA has the property of magnetism, photocatalytic degradation and adsorption. The adsorption isotherms and adsorption kinetics of rhodamine B and malachite green are determined. The maximum adsorption amounts of the Rhodamine B and malachite green are 475.49 mg/g and 646.82 mg/g, respectively. The photodegradation removals of rhodamine B and malachite green are close to 1, which is attributed to the adsorption performance of MSPA, and synergy between adsorption and photodegradation. The photocatalytic degradation mechanism is detailed investigated. MSPA can be quickly recycled from aqueous solution under extra magnetic field after use. The present work demonstrates that the waste cotton stem is converted into promising MSPA for dye wastewater removal. Graphical abstract: The schematic of dye wastewater removal by the MSPA. Unlabelled Image Highlights: MSPA is successfully prepared using one-pot. MSPA exhibits efficiency adsorption and photocatalytic degradation of dye. Synergy between activated carbon and ZnO contributes to dye removal. MSPA can be quickly recycled from dye wastewater after use.